Form as an Epiphany of Matter… (XXI Century. Spanish Literature and Culture, 2004)
Through a comparison, Virginia Trueba Mira gathers together the works and thoughts ofValente and Tàpies, focusing on aspects such as the light, always referred to as creating light;fragmentism that offers a more approachable vision of the world or the aesthetics of poverty andValente’s new vision, of whom she says does not copy his artistic reference but considers the formationof the painting-body, which is, its vertex.
Keywords: Valente; Tàpies; comparison; poetry; painting